List-level control in the flanker task. Issue 9 (September 2020) - Bugg, Julie M; Gonthier, Corentin
Current theories posit multiple levels of cognitive control for resolving conflict, including list-level control: the global or proactive biasing of attention across a list of trials. However, to date, evidence for pure list-level control has largely been confined to the Stroop task. Our goals were twofold: (a) test the generality of theoretical accounts by seeking evidence for list-level control in the letter flanker task, using an established method involving diagnostic items, and investigating the conditions under which list-level control may and may not be observed and (b) develop and test a potential solution to the challenge of isolating list-level control in tasks with a relatively limited set of stimuli and responses such as arrow flanker. Our key findings were that list-level control was observed for the first time in a letter flanker task on diagnostic items (Experiment 1), and it was not observed when the design was altered to encourage learning and use of simple stimulus–response associations (Experiment 2). These findings support the generalisability of current theoretical accounts positing dual-mechanisms or multiple levels of control, and the associations as antagonists to control account positing that list-level control may be a last resort, to conflict tasks besides Stroop. List-level control was also observed in the arrow flanker task using a modified design (Experiment 3), which could be extended to other conflict tasks with limited sets of stimuli (four or fewer), although this solution is not entirely free of confounds.